Utilization of antibiotics among physicians in the general outpatient unit of a tertiary health facility in North Central Nigeria (Bangladesh Journal of Medicine, 2018)
Background: Antibiotics are prescribed to treat infections caused by suspected or confirmed organism(s). Inappropriate antibiotic prescribing could lead to treatment failure increase cases of toxicity and development of resistant strains of organism.Objective: To assess the pattern of antibiotics prescribing among physician in the General Outpatients Department of University of Ilorin Teaching Hospital in Ilorin.Method: The study involved a 6 month retrospective review of prescription sheets in the General Outpatient Department of University of Ilorin Teaching Hospital (UITH) to assess the prescription pattern. A total of 3,552 prescriptions were reviewed. Information on prescribing pattern of physicians and patient demographics were obtained through a date collection form. The data obtained were entered into Statistical Package for Social Scientists (SPSS) version 16 and analyzed using descriptive value. Logistic regression was used in inferential statistic and P values Â 0.05 were considered significant.Results: The prescribing rate of antibiotic was 82.13%. The most widely prescribed antibiotics were amoxicillin/ clavulanic acid (21.9%), ciprofloxacin (21.2%), metronidazole (17.2%) and Amoxycillin (9.4%). Average number of drugs per prescription was 4.32 ±1.46. There was significant difference in the prescribing duration of antibiotics in female compare to male patient. Female patients had longer duration than their male counterpart.Conclusion: There was high rate of antibiotic prescribing among physicians in the health facility. Rational prescribing in terms of generic prescribing and prescribing from Essential Drug List (EDL) was adequately complied with and the number of prescribed medications per prescription was within the limit.Bangladesh J Medicine Jul 2017; 28(2) : 64-69